The Effect of Variety and Growing Conditions on the Chemical Composition and Nutritive Value of Wheat for Broilers - Ball, M. E. E. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
The aim of this study was to examine the effect of variety and growing conditions of wheat on broiler performance and nutrient digestibility. One hundred and sixty-four wheat samples, collected from a wide range of different sources, locations, varieties and years, were analyzed for a range of chemical and physical parameters. Chemical and physical parameters measured included specific weight, thousand grain weight (TG), in vitro viscosity, gross energy, N, NDF, starch, total and soluble non-starch polysaccharides (NSP), lysine, threonine, amylose, hardness, rate of starch digestion and protein profiles. Ninety-four of the wheat samples were selected for inclusion in four bird trials. Birds were housed in individual wire metabolizm cages from 7 to 28 d and offered water and feed ad libitum. Dry matter intake (DMI), live weight gain (LWG) and gain:feed were determined weekly. A balance collection was carried out from 14 to 21 d for determination of apparent metabolizable energy (AME), ME:gain, DM retention, oil and NDF digestibility. At 28 d the birds were sacrificed, the contents of the jejunum removed for determination of in vivo viscosity and the contents of the ileum removed for determination of ileal DM, starch and protein digestibility. The wheat samples used in the study had wide-ranging chemical and physical parameters, leading to bird DMI, LWG, gain:feed, ME:GE, AME content and ileal starch and protein digestibility being significantly (p<0.05) affected by wheat sample. A high level of N fertilizer application to the English and NI wheat samples tended to benefit bird performance, with increases of up to 3.4, 7.2 and 3.8% in DMI, LWG and gain:feed, respectively. Fungicide application also appeared to have a positive effect on bird performance, with fungicide treated (+F) wheat increasing bird DMI, LWG and gain:feed by 6.6, 9.3 and 2.7%, over the non-fungicide treated (-F) wheats. An increase (p<0.1) of 9.3% in gain:feed was also observed at the low seed rate of 40 compared to 640 seeds/m(2). It was concluded that the type of wheat sample and environmental growing conditions significantly affects bird performance when fed wheat-based diets.